1966
DOI: 10.1002/1097-0142(196607)19:7<891::aid-cncr2820190702>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the cervix. A clinicopathologic study of 47 cases

Abstract: In a review of cervical carcinoma at Magee‐Womens Hospital during a 14‐year period only 47 (5%) of 942 cases admitted for treatment were of the glandular variety. The difficulties encountered in the clinical, cytological and histological diagnosis of this type of cervical neoplasm are discussed. There appeared to be no unanimity concerning the histological criteria for diagnosis but the most frequent microscopic patterns encountered in this study were the papillary and well‐differentiated cervical gland type. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…For cervical adenocarcinoma, there is no solid evidence regarding the most effective treatment approach (28). Many studies report that the use of RT within the pelvis is more effective for suppressing squamous cell carcinoma than adenocarcinoma (29)(30)(31)(32). A recent study reported no appreciable difference in the 5-year survival rate when RT, including CCRT, was compared with CT alone in the postoperative treatment of stages Ib-IIb cervical adenocarcinoma (33).…”
Section: Discussionmentioning
confidence: 99%
“…For cervical adenocarcinoma, there is no solid evidence regarding the most effective treatment approach (28). Many studies report that the use of RT within the pelvis is more effective for suppressing squamous cell carcinoma than adenocarcinoma (29)(30)(31)(32). A recent study reported no appreciable difference in the 5-year survival rate when RT, including CCRT, was compared with CT alone in the postoperative treatment of stages Ib-IIb cervical adenocarcinoma (33).…”
Section: Discussionmentioning
confidence: 99%
“…The present Korean series has been analysed without respect to pre-or post-menopausal state; we had incomplete information on this and other clinical factors in a number of patients, and the subdivision of the cases has been based on conventional histological criteria only. Nielson et al (24) give the peak age incidence in cases of intra-epithelial carcinoma in the [30][31][32][33][34][35][36][37][38][39] bracket, and the mode of the age distribution was at 40 years in 140 Swedish cases 1921-53 (13). The age range is wide, however, and according to Hertig & Gore (10) from the twenties to the seventies.…”
Section: Discussionmentioning
confidence: 99%